Exploring athletic identity in elite-level English youth football: a cross-sectional approach - Mitchell, T. O.; Nesti, M.; Richardson, D.; Midgley, A. W.; Eubank, M.; Littlewood, M. (Journal of Sports Sciences, 2014)
This study is the first empirical investigation that has explored levels of athletic identity in elite-level English professional football. The importance of understanding athletes` psychological well-being within professional sport has been well documented. This is especially important within the professional football industry, given the high attrition rate (Anderson, G., & Miller, R. M. (2011). The academy system in English professional football: Business value or following the herd? University of Liverpool, Management School Research Paper Series. Retrieved from http://www.liv.ac.uk/managementschool/research/working%20papers/wp201143.pdf) and distinct occupational practices (Roderick, M. (2006). The work of professional football. A labour of love? London: Routledge). A total of 168 elite youth footballers from the English professional football leagues completed the Athletic Identity Measurement Scale (AIMS). Multilevel modelling was used to examine the effect of playing level, living arrangements and year of apprentice on the total AIMS score and its subscales (i.e., social identity, exclusivity and negative affectivity). Football club explained 30% of the variance in exclusivity among players (P = .022). Mean social identity was significantly higher for those players in the first year of their apprenticeship compared to the second year (P = .025). All other effects were not statistically significant (P > .05). The novel and unique findings have practical implications in the design and implementation of career support strategies with respect to social identity. This may facilitate the maintenance of motivation over a 2-year apprenticeship and positively impact on performance levels within the professional football environment.